Contribution of Speed and Agility to Futsal Dribble Skills in the Men's Futsal Team at the Riau Taxation Vocational School.: Kontribusi Kecepatan Dan Kelincahan Terhadap Keterampilan Dribble Futsal Pada Tim Putra SMK Perpajakan Riau - Irma, Ade; Sari, Merlina (Jurnal Olahraga dan Kesehatan (ORKES), 2024)
The aim of this research is to determine the contribution of speed and agility to futsal dribbling skills in the Men's Futsal Team at the Riau Taxation Vocational School. This type of research is multiple correlation. The population in this study was the Boys Futsal Team of the Riau Taxation Vocational School, totaling 20 people. The sampling technique used was total sampling so that the sample in this study was 20 people. The research instruments used were the dodging run test, shuttle run test and futsal dribbling test. The data analysis technique used is the multiple correlation value test and calculating the contribution value. (1) There is a speed contribution to futsal dribbling skills in the Men's Futsal Team players at the Riau Taxation Vocational School with a value of rcount = 0.587 ≥ rtable = 0.444 with a contribution value of 34.46%, (2) There is no contribution of agility to futsal dribbling skills in Team players Son of Futsal at Riau Taxation Vocational School with a value of rcount = 0.727 ≥ rtable = 0.444 with a contribution value of 52.85%. (3) There is a contribution of speed and agility to the futsal dribbling skills of the Men's Futsal Team players at the Riau Taxation Vocational School with a value of rcount = 0.752 ≥ rtable = 0.444 or 56.55%.